Coalescence of teeth in fishes - Britski, Heraldo A.; Andreucci, Roberto D. [UNESP]; Menezes, Naércio A.; Carneiro, José (Sociedade Brasileira de Zoologia, 1984)
In this paper the concept of coalescence of teeth previously defined for the Tetraodontoid fishes is extended to some other teleostomes. Comments are made on the «dentigerous plates» of non-teleostomian fishes and on the dermal plates bearing odontodes found in some fossil groups.